After Ancient Biography - Fraser, Robert (Springer International Publishing, 2020)
1. Chapter I: Paris in Parallel: Classical Biography in an Age of Revolution – 2. Chapter II: Ancient Biographers and Modern Classicists: “What is Truth?” – 3. Chapter III: Biography as Representation: Plutarch’s Parallel Lives – 4. Chapter IV: Biography as Censure: Suetonius and Procopius – 5. Chapter V: Biography as Persuasion: The Christian Gospels – 6. Chapter VI: Biography as Inner Drama: Athanasius’s Life of Saint Antony – 7. Chapter VII: Heroic Biography: Carlyle & Co. – 7. Chapter VIII: Caustic Biography: Strachey & Co. – 8. Conclusion: “Beauty is Terror”. Marrying life-writing with classical reception, this book examines ancient biography and its impact on subsequent ages. Close readings of ancient texts are framed by an assessment of their influence on the age of the French Revolution and Napoleon, and on the nineteenth, twentieth, and twenty-first centuries, of responses to ancient biography of modern critics, and of its visible legacy in art and film. Crucially it asks what modern biographers can learn from their ancient predecessors. Are the challenges involved in life-writing still the same? Have working methods changed, and in what ways? What in the context of biographical writing is truth, and how are its interests best served? How is it possible, now as then, honestly to convey a life?
10.1007/978-3-030-35169-4
Keywords: Literature—History and criticism.; Classical literature.; Literature—Philosophy.